Mapping Race: Historicizing the History of the Color-Line - Irwin, Ryan M. (History compass, 2010)
This study examines scholarship about the global color-line. It unfolds in two sections. The first traces how understandings of race and racism were encoded within university environments in the mid-twentieth century. The second shows how this epistemology influenced early academic comparisons of the United States and South Africa in the 1980s and why the literature diversified in the post-apartheid era.